Explaining U.S. Immigration 1971-98 - Clark, Ximena; Hatton, Timothy J.; Williamson, Jeffrey G. (World Bank, Washington, DC, 2013)
The authors develop and estimate a model explaining the level and country-source composition of United States immigration since the early 1970s. The model incorporates ratios of source country income, education, and demographic structure, as well as relative inequality. The authors' model also incorporates both network effects, as reflected in the stock of previous immigrants, and various controls for immigration quota policy. The model is estimated on a panel of 81 source countries for 1971-98. The results strongly support the influence of economic, demographic, and geographic variables as well as policy. The regression results are used to identify those factors that most influenced the changing composition of U.S. immigration by source.